EXPLORING LEARNING MEDIA USED BY ENGLISH TEACHER AT SDN 2 BENGKALA FOR INCLUSIVE EDUCATION - I Made Kusuma Yudha (Berajah Journal, 2026)
This article reports a qualitative study on learning media used by an English teacher at SDN 2 Bengkala to support inclusive education, particularly for students with hearing and speaking impairments. The study addresses three questions: the types of learning media used in inclusive English instruction, the challenges faced by the teacher, and the strategies used to overcome those challenges. Data were collected through classroom observation, semi-structured interviews, documentation, and anecdotal records, then analyzed using thematic analysis. The findings show that visual and digital media were central to English instruction. PowerPoint slides, projected pictures, short videos, tablets, flashcards, posters, realia, wall displays, and whiteboard illustrations helped make vocabulary and classroom concepts more concrete. However, the implementation of media was constrained by limited devices, uneven digital skills, the need to simplify complex materials, and the limited availability of academic sign language vocabulary. The teacher responded through practical adaptation: simplifying visuals, adding written explanations, using familiar tools, seeking support from colleagues and assistant teachers, applying flexible grouping, and encouraging peer support. The study suggests that inclusive English teaching depends not only on the availability of media but also on teacher creativity, collaborative support, and accessible visual design.